Regional energy transition path and the role of government support and resource endowment in China. (March 2023) - Su, Xiang; Tan, Junlan
Abstract: This study explores the impact of government support and resource endowment (geographical location, climatic conditions, natural resource reserves) on regional energy transitions in China. Thirty regions in China were taken as the study areas, and data samples were selected from 2007 to 2020. The system Generalized method of moments model was employed to outline the path for regional energy transition. The conclusions are as follows. (1) Resource endowment at the national level inhibits energy transition, and the resource endowment in the eastern, central and western regions of China inhibits energy transition. The central region has the strongest inhibitory effect, and the eastern region has the weakest. (2) Policy support can significantly promote energy transition, with the best effects in the central region and the weakest effects in the east. (3) Technological innovation has significantly promoted energy transformation; however, the impact on the western region is not significant. The urbanization level in the eastern region can promote the energy transformation, yet the urbanization level in the central and western regions and the whole country inhibits the energy transformation. Moreover, the tertiary industry will stimulate the energy transformation, and the stimulating effect gradually weakens from east to west. Finally, foreign direct investmentcan promote the energy transition, and the promotion effect of the central region is better than that of the east and west. The research in thiswork provides an important theoretical reference for realizing China's energy transition. Graphical abstract: Results of government support and resource endowment on energy transition. Image 1 Highlights: Resource endowment affect energy transition difference in different regions. Policy support can reduce traditional fossil energy consumption in all regions. GMM model is used to explore the relationships between variables. Policy support for regional energy transformation are provided.